ChemInform Abstract: From Protein Engineering to Immobilization: Promising Strategies for the Upgrade of Industrial Enzymes. Issue 6 (11th February 2014) - Singh, Raushan Kumar; Tiwari, Manish Kumar; Singh, Ranjitha; Lee, Jung‐Kul
Abstract Review: 279 refs.